Spatio-temporal expansion patterns and influencing factors in China’s new local retail industry: A case study of Luckin Coffee - Qi, FengXun; Qin, WeiShan; Li, Xiaohan (PloS one, 2025)
with the increased penetration of the Internet, artificial intelligence, and other technologies, New Retail, an emerging commercial sector in cities, has gained significant momentum. As a new local retail brand in China, Luckin Coffee has actively explored the new retail model and rapidly captured the market. Its expansion strategy and influence mechanisms are worth exploring in depth. Based on point of interest (POI) data of China’s Luckin stores (2018–2023), this study constructs a geographical indicator system and employs spatial analysis and factor detection methods to study the evolution of Luckin Coffee’s resource agglomeration patterns and its formation mechanism. The results indicate the following: (1) Luckin Coffee’s layout in China exhibits a highly concentrated and unbalanced spatial distribution pattern, showing an expansion trend from coastal regions toward inward diffusion, with most stores located in economically developed areas such as urban agglomerations and first- and second-tier cities; (2) Luckin Coffee’s spatial expansion pattern has progressed through the three phases: initially dominated by hierarchical diffusion, then by a combination of hierarchical and contact diffusion, and finally by contact diffusion, (3) the spatial differentiation in the number of Luckin Coffee stores results from the interplay of multiple factors. However, the influence of each factor on spatial differentiation varied significantly. Specifically, urban construction levels and consumption capacity within the second geographic area, along with informatization levels and human capital in the third geographic area, exhibit the greatest explanatory power regarding spatial distribution. (4) The impact of primary influencing factors on Luckin Coffee’s spatial distribution revealed spatial variability, with notable local imbalances. These imbalances are significant, and the analyzed units with relevant influences exhibit block and band aggregation characteristics. This study provides empirical evidence to supplement current research on the spatial expansion patterns and influence mechanisms of New Retail brands in China.